Review of global 2.1-1.8 Ga orogens: implications for a pre-Rodinia supercontinent - Zhao, G C; Cawood, Peter Anthony; Wilde, S A; Sun, M (2002)
Available lithostratigraphic, tectonothermal, geochronological and paleomagnetic data from 2.1-1.8 Ga collisional orogens and related cratonic blocks around the world have established connections between South America and West Africa Western Australia and South Africa; Laurentia and Baltica; Siberia and Laurentia; Laurentia and Central Australia; East Antarctica and Laurentia, and North China and India. These links are interpreted to indicate the presence of a supercontinent existing before Rodinia, referred to herein as Columbia, a name recently proposed by Rogers and Santosh [Gondwana Res. 5 (2002) 5] for a Paleo-Mesoproterozoic supercontinent. In this supercontinent, the Archean to Paleoproterozoic cratonic blocks were welded by the global 2.1-1.8 Ga collisional belts. The cratonic blocks in South America and West Africa were welded by the 2.1-2.0 Ga Transamazonian and Eburnean Orogens; the KaapvaaI and Zimbabwe Cratons in southern Africa were collided along the similar to2.0 Ga Limpopo Belt; the cratonic blocks of Laurentia were sutured along the 1.9-1.8 Ga Trans-Hudson, Penokean, Taltson-Thelon, Wopmay, Ungava, Torngat and Nagssugtoqidian Orogens; the Kola, Karelia, Volgo-Uralia and Sarmatia (Ukrainian) Cratons in Baltica (Eastern Europe) were joined by the 1.9-1.8 Ga Kola-Karelia, Svecofennian, Volhyn-Central Russian and Pachelma Orogens; the Anabar and Aldan Cratons in Siberia were connected by the 1.9-1.8 Ga Akitkan and Central Aldan Orogens; the East Antarctica and an unknown confidential block were joined by the Transantarctic Mountains Orogen; the South and North Indian Blocks were amalgamated along the Central Indian Tectonic Zone; and the Eastern and Western Blocks of the North China Craton were welded together by the similar to1.85 Ga Trans-North China Orogen. The existence of Columbia is consistent with late Paleoproterozoic to Mesoproterozoic sedimentary and magmatic records. The similar to2.0 Ga fluvio-deltaic deposits have been found in all cratonic blocks in South America and West Africa, and ...